Profil of Students' Mathematical Problem Solving Ability with the Implementation of CRA-Adjacent Inquiry Learning In Terms of Adversity Quotient - Putri, Rafika; Isnarto, Isnarto; Suyitno, Amin (Unnes Journal of Mathematics Education Research, 2023)
The purpose of this study was to describe the profile of students' mathematical problem-solving abilities in terms of adversity quotient. This research is qualitative research with data triangulation. The population of this study were class VIII students of SMP Negeri 13 Semarang for the 2022/2023 academic year. Determination of research subjects using purposive sampling technique, to obtain 6 subjects, namely two categories of climbers, two categories of campers, and two categories of quitters. The results of this study are students in the climbers category are able to master all stages of Polya with the NCTM indicator, namely carrying out steps to understand the problem, develop a problem solving plan, carry out problem solving, and re-check the results of the settlement, students in the campers category are able to master three of the four stages of Polya with the NCTM indicator, namely carrying out steps to understand the problem, develop a problem solving plan, and carry out problem solving, and students in the quitters category are able to master two of the four stages of Polya with the NCTM indicator, namely carrying out steps to understand the problem and develop a problem solving plan.